SYNTHESIS OF AG0 NANOPARTICLES FROM EXTRACT AND ETHANOLIC AND AQUEOUS FRACTIONS OF LEAVES AND PETALS OF HIBISCUS ROSA-SINENSIS L. - Sayes Reátegui, Carolina Ginett; Herrera Hernández, Nora G.; Huarote, Emily (Journal of the Chilean Chemical Society, 2022)
The synthesis of nanoparticles from plant extracts has become an interesting line of research in recent years. The purpose of the study was the synthesis of silver nanoparticles (NSP) from silver nitrate, aqueous and ethanol 80% extracts obtained by ultrasound-assisted extraction, as well as fractions of chloroform, ethyl acetate and water, of flower petals and leafs of Hibiscus rosa-sinensis L. The ethanolic extract of petals of H. rosa-sinensis L. was analyzed by UHPLC-ESI-Q-Orbitrap-MS/MS identifying pelargonidin, petunidin, kaempferol, luteolin and orientin. Characterization of NSP by UV-Visible spectrophotometry gave a lmax at 400,631 nm and 389,411 nm for NSP obtained with ethanolic extract of flower petals and leafs, lmax at 402,270 nm and 391,057 nm for NSP of aqueous extracts of flower petals and leafs respectively. FTIR confirmed the reduction of Ag+ ions to Ag0 ions in NSP. Dynamic light dispersion (DLS) showed an effective diameter of the NSP from extracts, less than 80 nm and for NSP from fractions was less at 53 nm and near-zero polydispersity indices. Electron field emission scanning microscopy (FE-SEM) showed a particle size between 17 - 32 nm for NSP from extracts, and 15 - 26 nm for NPS from fractions, which showed a spherical structure. Energy dispersion X-ray spectroscopy (EDS) confirmed the elemental composition of NSP showing mostly silver (60.44%), oxygen (32.48%) and potassium (4.97%). This study revealed that the compounds from the extracts of Hibiscus rosa-sinensis L. are good reducing and stabilizing agents for the synthesis of silver nanoparticles, being pH 9 optimal for synthesis.